Marriage and Morals - Russell, Bertrand (London Routledge, 2015)
Offers a cross-cultural examination of individual, familial and societal attitudes towards sex and marriage. Exploring the codes by which we live our sexual lives and conventional morality, this title sets out a fresh morality, shaped and influenced by dramatic changes in society such as the emancipation of women and the use of contraceptives.
Keywords: Interpersonal relations -- Marriage -- Marriage--Moral and ethical aspects